Studies on Incorporation of 14C into Carrageenan and Methods of Localizing Carrageenan in Animal Tissues - Richer, Suzanne M. (My University, 1971)
Lambda carrageenan when injected subcutaneously causes the formation of a connective tissue granuloma. Initially there is a proliferation of connective tissue elements up to about fourteen days followed by regression so that by six weeks most collagenous tissue has disappeared and been replaced by adipose tissue. Lambda carrageenan has been identified in the granuloma by staining reactions with toluidine blue and other stains for acid polysaccharides. The present study was undertaken to localize the carrageenan by means of fluorescent antibody and autoradiography. For this purpose labelling of carrageenan by photoassimilation of 14CO2 into carrageenan was done. Different parameters affecting the incorporation of 14C into the carrageenan fractions were studied.
Keywords: Carrageenan, incorporation, localizing, animal, tissues, Lambda, polysaccharides, photoassimilation